Device and method matter: A critical evaluation of eccentric hamstring muscle strength assessments - Wiesinger, H.-P.; Gressenbauer, C.; Kösters, A.; Scharinger, M.; Müller, E. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Equivocal findings exist on isokinetic and Nordic hamstring exercise testing of eccentric hamstring strength capacity. Here, we propose a critical comparison of the mechanical output of hamstring muscles as assessed with either a dynamometer (IKD) or a Nordic hamstring device (NHD). Twenty-five volunteers (26 ± 3 years) took part in a counterbalanced repeated-measures protocol on both devices. Eccentric peak torque, work, angle of peak torque, bilateral strength ratios, and electromyography activity of the biceps femoris long head, semitendinosus and gastrocnemius muscles were assessed. There was a very poor correlation in eccentric peak torque between the devices (r < 0.58), with a systematic and proportional bias toward lower torque values on the IKD (~28%) and a high typical error (~19%) in IKD and NHD measurements comparison. Furthermore, participants performed a higher total eccentric work on IKD, reached peak torques at greater knee extension angles, and showed a greater side-to-side strength difference compared to the Nordic hamstring exercise. Gastrocnemius muscle activity was lower during the Nordic hamstring exercise. Reliability was low for work on NHD and for angle of peak torque and bilateral strength ratios on either device. We conclude that the evaluation of eccentric knee flexor strength depends on the testing conditions and even under standardized procedures, the IKD and NHD measure a different trait. Both tests have limitations in terms of assessing strength differences within an individual, and measurements of the angle of peak torque or side-to-side differences in eccentric knee flexor strength revealed low reliability and should be considered with caution.